Andrew Carnegie Builder Of Libraries - Simon, Charnan (New York Children's Press, 1997)
Describes the efforts of andrew carnegie to build public libraries as a way of improving community life in pittsburgh and other places
American Corner
Includes Bibliographical referencesand index
11
Keywords: Carnegie Libraries -- History; Public Libraries